Quantifying conditioned place preference: a review of current analyses and a proposal for a novel approach - Yates, Justin R. (Frontiers in Behavioral Neuroscience, 2023)
Conditioned place preference (CPP) is used to measure the conditioned rewarding effects of a stimulus, including food, drugs, and social interaction. Because various analytic approaches can be used to quantify CPP, this can make direct comparisons across studies difficult. Common methods for analyzing CPP involve comparing the time spent in the CS + compartment (e.g., compartment paired with drug) at posttest to the time spent in the CS + compartment at pretest or to the CS -compartment (e.g., compartment paired with saline) at posttest. Researchers can analyze the time spent in the compartment(s), or they can calculate a difference score (CS + post -CS + pre) or (CS + post -CS -post) or a preference ratio (e.g., CS + post/(CS + post + CS -post)). While each analysis yields results that are, overall, highly correlated, there are situations in which different analyses can lead to discrepant interpretations. The current paper discusses some of the limitations associated with current analytic approaches and proposes a novel method for quantifying CPP, the adjusted CPP score, which can help resolve the limitations associated with current approaches. The adjusted CPP score is applied to both hypothetical and previously published data. Another major topic covered in this paper is methodologies for determining if individual subjects have met criteria for CPP. The paper concludes by highlighting ways in which researchers can increase transparency and replicability in CPP studies.